meta analisis Pengaruh Metode Hypnoteaching terhadap beberapa hasil pembelajaran - Indra Darmawan; Burhanudin Tolla; Yetti Supriyati (Jurnal Evaluasi Pendidikan, 2021)
The purpose of this study was to re-analyze the effect of the Hypnoteaching learning method on several learning outcomes. The method used in this research is meta-analysis. The research begins by tracing the relevant research results for analysis. Data was collected by searching electronic journals through Google Scholar and Google Scholar with the keywords "hypnoteaching" and Experiment ". From that search, 15 articles were obtained but only 11 were eligible from journals. Data were analyzed using the calculation of the effect size using the formula. Based on the results of the analysis, the hyonoteaching learning method was able to increase the effect of student learning outcomes as evidenced by the cohen d value (1.95).